2021
DOI: 10.1186/s12912-021-00539-w
|View full text |Cite
|
Sign up to set email alerts
|

“I am called girl, but that doesn’t matter” -perspectives of male nurses regarding gender-related advantages and disadvantages in professional development

Abstract: Background Exploration of professional development experiences of male nurses can help develop evidence-based strategies to attract males into nursing. The study aims to investigate the advantages and disadvantages of being a male in nursing profession that male nurses and male nursing students experience in their professional development. Methods A descriptive qualitative research was designed. Purposive sampling was applied and 24 males (12 nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 22 publications
9
69
0
Order By: Relevance
“…Both Blackley et al (2019) and Santos and Amâncio (2019) reported that men were being pushed away from direct patient care by continual negative stereotyping due to the feminizing of the nursing profession, resulting in role conflict among men (Blackley et al, 2019; Schubert, 1997; Whittock & Leonard, 2003). In addition, men were also reported to experience being pulled away from direct clinical care to non‐clinical roles within and outside the nursing profession (Mao et al, 2021; Schubert, 1997; Williams, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Blackley et al (2019) and Santos and Amâncio (2019) reported that men were being pushed away from direct patient care by continual negative stereotyping due to the feminizing of the nursing profession, resulting in role conflict among men (Blackley et al, 2019; Schubert, 1997; Whittock & Leonard, 2003). In addition, men were also reported to experience being pulled away from direct clinical care to non‐clinical roles within and outside the nursing profession (Mao et al, 2021; Schubert, 1997; Williams, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 studies, five were quantitative and employed cross‐sectional designs (Anderson, 1987; Andrews et al, 2012; Brown & Jones, 2004; Liu et al, 2015; Lou et al, 2010; Schubert, 1997); six studies used qualitative approaches (Blackley et al, 2019; Mao et al, 2021; Santos & Amâncio, 2019; Whittock & Leonard, 2003; Williams, 1995; Wingfield, 2009) including phenomenology (Blackley et al, 2019) and descriptive qualitative (Mao et al, 2021). Four studies (Santos & Amâncio, 2019; Whittock & Leonard, 2003; Williams, 1995; Wingfield, 2009) did not explicitly state the qualitative approach used.…”
Section: Resultsmentioning
confidence: 99%
“…These findings were consistent with those reported in previous studies in which there were differences in knowledge between male and female nurses in different countries including knowledge about COVID-19 [ 22 , 29 , 41 , 43 , 45 47 ]. Traditionally, nursing was viewed as more suitable for female nurses, however, recent qualitative studies have reported that male nurses perceive the profession equally suitable compared to their female counterparts [ 63 ]. Probably, more studies are needed to understand why female nurses tend to score more in knowledge tests compared to male nurses and how to improve knowledge of male nurses in certain domains to thrive in their professional development.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the medical equipment in university hospitals exemplifies advanced high technology, and the challenge of technology and modern equipment motivates male nurses. Female nurses are also expected to have more male nurses to assist them in operating medical equipment and devices in special nursing units (Mao et al, 2021). Therefore, male nurses feel that they are valuable to their unit and organization, leading to greater job satisfaction, resulting in perceived ITS.…”
Section: Discussionmentioning
confidence: 99%